Determination of Impurities in New Promising Antioxidants Bis-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propyl]sulfide and Dodecyl(3,5-dimethyl-4-hydroxybenzyl)sulfide - T. G. Shinko; S. V. Terentyeva; S. Ye. Yagunov; N. V. Kandalintseva; O. I. Prosenko; Ye. A. Ivanovskaya; P. I. Pinko (Разработка и регистрация лекарственных средств)
Introduction. Dodecyl(3,5-dimethyl-4-hydroxybenzyl)sulfide (T1) and bis-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propyl]sulfide (T2) are the collaborative development of Novosibirsk State Pedagogical University and Novosibirsk Research Institute of Antioxidants. It was revealed in several experiments and research works that these substances have antioxidant, anti-inflammatory, hepatoprotective, cytoprotective, haemorheological activities. These facts make the objects of study promising medicinal antioxidant drugs. Consequently it’s necessary for the future production quality control to have standards and analytical methods for substances analysis.Aim. Impurities methods development and validation for the new biologically active substances T1 and T2.Materials and methods. HPLC method with UV-detection on 278 nm was carried out for the determination of impurities in objects of study. HPLC analysis were performed on ZORBAX SB-C18 (5 μm, 150 × 4,6 mm) column with isocratic regimen and with use of the acetonitrile:water mixture (T1) or acetonitrile (T2) as a mobile phase.Results and discussion. It was find out, that T1 has two unidentified impurities with concentration not more than 0,1 % during the shelf life. The chromatogramm of T2 has a peak of by-product of synthesis T2 – bis-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propyl]disulfide (T2-DS). Biologically safety of T2-DS was demonstrated in the previous works and the concentration of T2-DS was established to be not more, than 2,5 %. Furthermore, there was the one more unidentified impurity with concentration less, than 0,1 % on the chromatogram of T2. The developed HPLC methods were validated on characteristics «specificity», «linearity», «precision», «limit of quantification», «accuracy», «range».Conclusion. Methods for the determination of impurities in T1 and T2 were validated on the listed parameters. All the results meet the acceptance criteria: peaks on the chromatogramms are clearly separated; the correlation coefficients (r) are not more, than 0,980; accuracy was proved by linearity parameters; the value of the relative standard deviation is less, than 5 %; the intermediate precision for the both methods was proved by Fisher’s criterion and Student’s t-test.